Load Capacity Factor and Environmental Quality: Unveiling the Role of Economic Growth, Green Innovations, and Environmental Policies in G20 Economies - Duran, Ivan A.; Saqib, Najia (International Journal of Energy Economics and Policy, 2024)
The study analyzes the impact of economic growth, green innovations in Information and Communication Technology (ICT), and environmental legislation on the Load Capacity Factor (LCF) in G20 countries, employing data from 1993 to 2021. A comprehensive econometric analysis emphasizes the essential function of strong environmental legislation and green ICT developments in improving LCF, hence promoting a sustainable harmony between economic activities and environmental well-being. The study indicates that the integration of green ICT solutions and the enhancement of environmental regulations are essential for promoting sustainable development. Policy recommendations encompass the augmentation of environmental tax measures, the promotion of renewable energy investments, and the application of thorough environmental assessments. These techniques are crucial for the G20 countries in order to attain enduring environmental sustainability with economic growth.